Предмет: Математика, автор: 0000000001319


Решите неравенства:
3) 2(x - 1) – 3(x + 2) < 6(1 + x);
4) 7(у + 3) — 2 (у + 2) = 2(5у + 1);

Ответы

Автор ответа: Tina1701
4

Ответ:

3)  x∈ ( -7; + ∞)

4) у = 3

Пошаговое объяснение:

3) 2(x - 1) – 3(x + 2) < 6(1 + x);

2х - 2 - 3х - 6 < 6 + x

2x - 3x - x < 6 + 6 + 2

-2x < 14

x > 14: (-2)

x> -7

x∈ ( -7; + ∞)

4) 7(у + 3) — 2 (у + 2) = 2(5у + 1)

7у + 21 - 2у - 4 = 10у + 2

7у - 2у - 10у = 2 + 4 - 21

- 5у = - 15

у = 3

Похожие вопросы
Предмет: Русский язык, автор: gulyaharisova